TEACHERS GUIDANCE AND COUNSELING EFFORTS IN IMPROVING STUDENT LEARNING CREATIVITY IN SMK NEGERI 1 BATANG ANGKOLA - Laila Tussifah Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2017)
The study was based on the creativity of the student's learning problems, school environment and the general problems of this study were defined as follows: (1) What is the guidance and counseling? (2) How does the teacher guidance and counseling efforts in enhancing creativity belajarm students in SMK Negeri 1 Batang Angkola? (3) What are the guidance and counseling teacher effort in improving students' creativity? (4) What is the result of efforts of guidance and counseling teachers in improving student learning creativity? , The goal is to obtain a picture of the increase in creativity for students at SMK Negeri 1 Batang Angkola through Guidance Services Group. The method used is qualitative research case studies (case studies). In the case study, which examined more narrow unit but profound. The steps in this research: First, the formulation of the objectives to be achieved clearly. The second stage of the approach to be used Third, the collection of data required in accordance with the draft that has been provided. Fourth, the data that has been collected reconstruction study units organized into coherent and integrated well and intact. Fifth, prepareresearch reports by avoiding personal bias of the researcher. The findings of this research are: guidance and counseling teacher effort in improving students' creativity is very good because with meningktaknya creativity of students in order to follow subjects. Based on the above findings, it was concluded that efforts BK teachers in improving student learning creativity can be said to be good. Similar studies should be done with a background of different contexts in order to compare the findings of this research.Key word: guidance and counseling, learning creativity.